An integrated approach for evaluating dynamics of urban eco-resilience in urban agglomerations of China. (February 2023) - Wang, Yongyang; Cai, Yanpeng; Xie, Yulei; Chen, Lei; Zhang, Pan
Highlights: Establishing a comprehensive index to identify urban ecological sources. The synthesis framework to evaluate the urban ecological resilience based on balance of robustness and redundancy. The dynamics change of ENs resilience with the existence of risk and disturbance from external shocks. Abstract: The resilience of the urban ecological network is an indispensable aspect of reflecting the recovery capacity after the external risk shock. Improving the resilience of the ecological network is conducive to enhancing the ecological benefits. However, the current studies are lack of resilience evaluation from a comprehensive perspective. Thus, in this study, taking three typical urban agglomerations as cases, a comprehensive evaluation framework was proposed to assess ecological network resilience. First, we selected the comprehensive reserve as ecological sources and combined them with ecological corridors to construct the ecological network. Then we evaluated the resilience of ecological networks from the perspectives of robustness and redundancy. Finally, we analyzed the resilience of the network under different importance nodes failed. The results showed that (1) the average values of the comprehensive reserve value (CRV) in three urban agglomerations were over than 0.8. (2) the resilience of ecological networks in three urban agglomerations was blow the optimal value throughout during the period from 1985 to 2020. (3) the resilience change trends of multiple urban agglomerations were significant differences after removing certain important nodes, indicating the current ecological network is redundant. The research will help to improve the evaluation of urban ecological resilience and enhance the improvement of sustainable urban management and ecological restoration.